2006
DOI: 10.1103/physrevb.73.125410
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between a single Pt atom and a carbon nanotube studied by density functional theory

Abstract: Using density functional theory with the generalized gradient approximation, we have studied the interaction between a single Pt atom and a carbon nanotube. The bridge adsorption site on the outer wall of nanotube is favorable. The curvature affects the binding strength. Compared to the larger nanotube, Pt could bind stronger to the outer wall of a small radius nanotube. For zigzag nanotube, the most stable site on the outer wall is the bridge site with the underlying CC bond being parallel to the axis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Fig. 1d shows the energetically most favorable conformation with Pt residing above the C2-C3 bond [34][35] with a Pt-C distance of 2.05 Å . The geometry of the tube is changed due to strong Pt-CNT interaction causing nonidentical diameters with 6.48 Å and 6.29 Å of the longest and the shortest ones, respectively.…”
Section: Energetics and Optimized Geometriesmentioning
confidence: 97%
“…Fig. 1d shows the energetically most favorable conformation with Pt residing above the C2-C3 bond [34][35] with a Pt-C distance of 2.05 Å . The geometry of the tube is changed due to strong Pt-CNT interaction causing nonidentical diameters with 6.48 Å and 6.29 Å of the longest and the shortest ones, respectively.…”
Section: Energetics and Optimized Geometriesmentioning
confidence: 97%
“…The trends for diffusion energy barriers follow the adsorption energy trends as shown on Figure . Interestingly, in the case of platinum or aluminium atom adsorption on CNT, a significant curvature effect was reported ,. For Pt, the adsorption energy was stronger on the outer wall than on the inner ones, and this adsorption energy increases when the tube diameter decreases.…”
Section: Types Of Carbon Materials For Single Atom Deposition and Natmentioning
confidence: 99%
“…Chen et al reported the interaction of Pt adatom on CNT with several radii. 371 The authors observed a decrease of the binding energies for larger CNTs and also a change on the binding geometry. Similar observation were reported by Menon et al, who studied the interaction of Ni on graphite, and (5,5) and (10,10) CNTs.…”
Section: D-metalsmentioning
confidence: 95%